2011
DOI: 10.1074/jbc.m110.210724
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of the IL-13-induced Human Eotaxin-3 Gene by CREB-binding Protein-mediated Histone 3 Acetylation

Abstract: The etiology of a variety of chronic inflammatory disorders has been attributed to the interaction of genetic and environmental factors. Herein, we identified a link between epigenetic regulation and IL-13-driven eotaxin-3 in the pathogenesis of chronic allergic inflammation. We first demonstrated that the cAMP-responsive element (CRE) site in the eotaxin-3 promoter affects IL-13-induced eotaxin-3 promoter activity. Furthermore, the CRE-binding protein-binding protein (CBP), a histone acetyltransferase, induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 64 publications
(55 reference statements)
1
44
0
2
Order By: Relevance
“…Expression of IL-13, a Th2 cytokine, is subjected to epigenetic regulation (Lim et al, 2011). TNF-␣ induces expression of adhesion molecules and vascular permeability (Lee et al, 2012).…”
Section: Down Regulation Of Dnmt1 Induces Vascular Leakage and Angiogmentioning
confidence: 99%
“…Expression of IL-13, a Th2 cytokine, is subjected to epigenetic regulation (Lim et al, 2011). TNF-␣ induces expression of adhesion molecules and vascular permeability (Lee et al, 2012).…”
Section: Down Regulation Of Dnmt1 Induces Vascular Leakage and Angiogmentioning
confidence: 99%
“…The mapping of two STAT6 binding sites roughly established the promoter proximal regions required for IL-13-induced transcriptional activation of CCL26 (30). Further analysis demonstrated a requirement for two co-activators, activating transcription factor 2 (ATF2) and the histone acetyltransferase cAMP-responsive element (CRE)-binding protein (CBP) (50). Chromatin immunoprecipitation (ChIP) assays indicated that STAT6, CBP, ATF2, and acetylated histone 3 bound within the same region of the CCL26 promoter in esophageal epithelial cells following IL-13 treatment (50).…”
Section: Epigeneticsmentioning
confidence: 99%
“…Further analysis demonstrated a requirement for two co-activators, activating transcription factor 2 (ATF2) and the histone acetyltransferase cAMP-responsive element (CRE)-binding protein (CBP) (50). Chromatin immunoprecipitation (ChIP) assays indicated that STAT6, CBP, ATF2, and acetylated histone 3 bound within the same region of the CCL26 promoter in esophageal epithelial cells following IL-13 treatment (50). Thus, IL-13 induces the formation of a multi-protein complex on the CCL26 promoter that includes CBP, leading to increases in acetylated histone 3 and opening of the CCL26 promoter for additional transcriptional machinery.…”
Section: Epigeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, histone modifications appear to play important roles in organizing the nuclear architecture, with consequent effects on the regulation of gene transcription. 4,12 Histone H3 lysine 9 trimethylation (H3K9me3) is a histone modification that occurs in the N-terminal of lysine residues. It has been correlated with tumor suppressor gene silencing in colorectal cancer, 13 hepatocellular cancer, 14 and breast cancer.…”
mentioning
confidence: 99%